PENGARUH METODE PEMBELAJARAN BRAINSTORMING TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DI KELAS IV SD NEGERI 106146 MULIOREJO TAHUN PEMBELAJARAN 2024/2025 - Sinurat, Tria Lestari; Lumban Gaol, Rumiris; Silaban, Patri Janson; Ambarwati, Nova Florentina; Dongoran, Jhonas (Jurnal Ilmiah Aquinas, 2025)
This study aims to determine the effect of the brainstorming learning method on the learning outcomes of fourth grade Pancasila Education students at SD Negeri 106146 Muliorejo Learning Year 2024/2025. The research method used is quantitative with a pre-experimental approach using a one group pretest-posttest design. Data collection techniques were carried out through tests, questionnaires, and documentation. Data were analyzed descriptively and inferentially with the help of SPSS, through normality test, correlation test, and t-test. The results showed that there was an increase in learning outcomes after the implementation of the brainstorming method. This proves that the brainstorming learning method has a positive effect on Pancasila Education learning outcomes.